One-year echocardiographic outcomes of transcatheter aortic valve implantation with or without predilatation of the aortic valve: insights from the multicenter, randomized DIRECT trial. (25th November 2020) - Karmpalioti, M; Benetos, G; Drakopoulou, M; Xanthopoulou, M; Stathogiannis, K; Latsios, G; Synetos, A; Kalantzis, C; Voudris, V; Kosmas, E; Mastrokostopoulos, A; Katsimagklis, G; et al.
Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) has become the standard of care for high-risk and inoperable surgical patients and a valid alternative in intermediate-risk patients with severe aortic stenosis.The DIRECT trial (Predilatation in Transcatheter Aortic Valve Implantation Trial) was a multicenter, randomized, clinical trial designed to evaluate the safety and efficacy of TAVI with or without balloon aortic valvuloplasty (BAV) in patients with symptomatic, severe aortic valve stenosis. Purpose: To compare the one year echocardiographic findings among patients, who underwent TAVI using a self-expanding valve with or without BAV. Methods: A total of 171 patients with severe aortic stenosis were randomly assigned at 4 tertiary centers to undergo TAVI with the use of self-expanding prostheses with (pre-BAV) or without pre-dilatation (no-BAV). Follow up transthoracic echocardiography was performed 1 year after TAVI. Results: Of 171 patients, 86 patients were randomized to pre-BAV group and 85 to no-BAV group. One year echocardiographic follow up was available in 146 patients. In one year follow up there was no significant difference between pre-BAV and no-BAV group in aortic valve area (1.84±0.39cm 2 vs. 1.85±0.44cm 2, p=0.79), peak aortic valve gradient (15.95±9.97 mmHg vs. 14.51±6.60 mmHg, p=0.35), mean aortic valve gradient (8.37±5.01 mmHg vs. 7.99±4.04 mmHg, p=0.64), aortic valve peak velocity (1.90±0.51 m/s vs. 1.80±0.42m/s, p=0.24), ejection fraction (54.19±8.36% vs. 53.19±9.58%, p=0.52) and pulmonary artery systolic pressure (41.86±14.34 mmHg vs. 40.71±12.40 mmHg, p=0.64). The incidence of moderate or severe paravalvular regurgitation (PVL) in 1 year follow up was 6.2% without significant difference between the 2 study groups (5.7% in the no-BAV group vs. 6.6% in the pre-BAV group, p=0.83). Conclusions: Direct transcatheter aortic valve implantation has no impact on one-year prosthesis function and PVL in patients undergoing TAVI with self-expanding valve Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic